2021
DOI: 10.3389/fnhum.2021.711279
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Complex Emotions Using EEG and Virtual Environment: Proof of Concept and Therapeutic Implication

Abstract: During the last decades, neurofeedback training for emotional self-regulation has received significant attention from scientific and clinical communities. Most studies have investigated emotions using functional magnetic resonance imaging (fMRI), including the real-time application in neurofeedback training. However, the electroencephalogram (EEG) is a more suitable tool for therapeutic application. Our study aims at establishing a method to classify discrete complex emotions (e.g., tenderness and anguish) eli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…AI, machine learning and deep learning have started gaining traction in all sorts of fields, not excluding neuroscience; EEG data is a primary mode of AI research into being able to classify/recognize emotions on new data from previous data [119][120][121][122] ; many different forms of machine learning, deep learning and neural networks have been used for this emotion classification purpose [123][124][125][126][127][128][129][130][131] . Leading with AI for music listeningemotional experience research will allow us to form tailored solutions to the mental health crisis we have currently through personalized, convenient therapeutic interventions in hospitals and related clinical settings paired with music listening [132][133][134][135][136][137][138] . Specifically, in future work we can pry into the topologies of subjects' latent neural dynamics with the most naturalistic snapshot of complex music listening and emotional experience: subjects/patients simply listening to the music, with their emotional experience predicted by a highaccuracy deep learning framework 131 , exempt of having to physically report their emotions, which can interfere with the latent neural dynamics of pure music listening and emotional experience, on a physical interface.…”
Section: Discussionmentioning
confidence: 99%
“…AI, machine learning and deep learning have started gaining traction in all sorts of fields, not excluding neuroscience; EEG data is a primary mode of AI research into being able to classify/recognize emotions on new data from previous data [119][120][121][122] ; many different forms of machine learning, deep learning and neural networks have been used for this emotion classification purpose [123][124][125][126][127][128][129][130][131] . Leading with AI for music listeningemotional experience research will allow us to form tailored solutions to the mental health crisis we have currently through personalized, convenient therapeutic interventions in hospitals and related clinical settings paired with music listening [132][133][134][135][136][137][138] . Specifically, in future work we can pry into the topologies of subjects' latent neural dynamics with the most naturalistic snapshot of complex music listening and emotional experience: subjects/patients simply listening to the music, with their emotional experience predicted by a highaccuracy deep learning framework 131 , exempt of having to physically report their emotions, which can interfere with the latent neural dynamics of pure music listening and emotional experience, on a physical interface.…”
Section: Discussionmentioning
confidence: 99%
“…While this issue has been acknowledged in some BCI papers [5][6][7] and it has been suggested that block-wise cross-validation should be the preferred approach [5,8], the effects of using k-fold CV in such scenarios has not been investigated, and it is not clear how significantly (and under what circumstances) it can overestimate true mental state separability. Furthermore, it is not clear if block-wise CV will actually accurately estimate class separability.…”
Section: Cross-validation Techniques For Offline Classificationmentioning
confidence: 99%
“…Eleonora De Filippi et al [ 12 ] used a strategy for distinguishing distinct complex emotions such as tenderness and anguish that can be gleaned from EEG. EEG-based affective computing uses varied proportions of emotion-based classification and is widely utilized in passive elicitation using single-modality stimuli.…”
Section: Introductionmentioning
confidence: 99%